Relationship between undergraduate students search skills and usage of electronic information resources in Ambrose Alli University (AAU) Nigerian - Iguehi Joy Ikenwe; Anthony Oboite Solomon (Folia Toruniensia)
This research work investigated the relationship between undergraduate search skills and usage of electronic information resources (EIRs) in Ambrose Ali University (AAU), Edo State, Nigeria. The population of the study was 1,798 final year undergraduate students of AAU for the 2023/2024 academic session, with a sample of 113 from three Faculties. Accidental sampling and throwing of a dice were the adopted sampling techniques.  The research instrument for data collection was a structured questionnaire, and data were analyzed using descriptive statistics of percentages, mean scores (x̄), and standard deviation (SD) for the research questions while Pearson Product Moment Correlation Co-efficient statistical method was used to test the hypothesis; and the data were presented in Tables. Findings showed that AAU undergraduate students can define their information needs and select articles with ease (x̄ = 3.46). They can use basic ICTs and possess basic search skills (x̄ = 3.08). While they mainly use OPAC (x̄ = 3.8), e-books (x̄ = 3.8), e-journals (x̄ = 3.6), online databases (x̄ = 3.8), e-thesis (x̄ = 3.0), and e-magazines (x̄ = 3.0), they use them for leisure (x̄ = 3.1), searching for internship opportunities (x̄ = 3.6), and class assignment (x̄ = 3.3). They encounter challenges like unavailability of relevant EIRs (x̄ = 3.3), lack of awareness of EIRs (x̄ = 3.4), inadequate searching skills (x̄ = 3.3), and high cost of internet access in their quest to use EIRs (x̄ = 3.1). Thus, the paper concluded that the undergraduate students of AAU possess the search skills and showed that here is a significant relationship between the search skills and the use of electronic information resources. The study recommended updates on the search skills and use, as well as provision of facilities to ensure equitable quality learning of the students.